Novel chitinolytic bacteria from the shrimp shell processing waste - Mashuri Masri; EKA SUKMAWATY; LASINRANG ADITIA (Society for Indonesian Biodiversity, 2021)
Abstract. Masri M, Sukmawaty E, Aditia L. 2021. Novel chitinolytic bacteria from the shrimp shell processing waste. Biodiversitas 22: 2672-2681. Chitinase is an enzyme that hydrolyzes chitin (?-1,4 Nsetyl-D-glucosamine polymer). Several types of microorganisms produce chitinase that contributes to basic science and application. The role of chitinase enzyme is widely utilized in various fields, such as health as an anti-tumor agent and agriculture as biological control agents in plant disease caused by fungus. The purpose of this study was to isolate novel chitinolytic bacteria from shrimp shell waste in Makassar, Indonesia, using the scatter plate method on chitin agar selective media incubated at 37°C for 3 days. The clear zone formation around the colony was marked as an indicator of chitinase activity performed by the certain isolate. Selection was carried out by recycling all isolates on chitin agar media, which were incubated at 37°C for 3 days and measured the chitinolytic index. Two of ten isolates produced the highest chitinolytic index, namely, KLA-2 (45) and KLA-4 (15) isolates. The molecular identification results showed that the KLA-2 and KLA-4 isolates were Lysinibacillus fusiformis strain WH22 and Brevibacillus reuszeri strain CMB-15, respectively. Therefore, novel chitinolytic bacteria that can produce chitinase enzyme from shrimp shell waste are L. fusiformis and B. reuszeri